Knockdown of microRNA-203 reduces cisplatin chemo-sensitivity to osteosarcoma cell lines MG63 and U2OS in vitro by targeting RUNX2. (7th September 2021) - Huang, Zhengxiang; Huang, Lintuo; Liu, Lue; Wang, Lu; Lin, Wenjun; Zhu, Xiongbai; Su, Wei; Lv, Chen
Abstract : Clinical studies have reported that miRNAs abnormal expression are associated with the generation of cisplatin-resistant to osteosarcoma. Our previous research found that miR-203 is downregulated in osteosarcoma cells and overexpressed miR-203 exerts antitumor properties on osteosarcoma cells. However, the role and mechanism of miR-203 in regulating the sensitivity of cisplatin in osteosarcoma cells remains unclear. This study aimed to investigate the effects of miR-203 in cisplatin therapy for osteosarcoma cells in vitro and determined the underlying mechanism. In this study, we found that miR-203 was significantly upregulated in osteosarcoma cells after exposure to cisplatin. miR-203 knockdown reduced the sensitivity of osteosarcoma cells to cisplatin by suppressing cell apoptosis, cell cycle arrest, and inducing invasion. Meanwhile, we found that miR-203 knockdown reduces the therapeutic sensitivity of osteosarcoma cells by upregulating RUNX2. Moreover, we found that RUNX2 silencing sensitizes osteosarcoma cells to chemotherapy treatment of cisplatin. In summary, our findings demonstrated that miR-203 knockdown reduces cisplatin chemo-sensitivity to osteosarcoma cells in vitro by targeting RUNX2, and speculated that miR-203 may be a target for drug resistance of osteosarcoma to cisplatin.